Values and COVID-19 worries: The importance of emotional stability traits. (November 2021) - Fischer, Ronald; Bortolini, Tiago; Pilati, Ronaldo; Porto, Juliana; Moll, Jorge
Abstract: We examined the relationship between emotional stability as a more stable personality trait and COVID-related worries with basic human values in a Brazilian sample (N = 578) that is strongly affected by COVID-19. We tested whether emotional stability would moderate the effect of infection and economic worries on personal values. In line with predictions, we found that infection worries were more strongly related to Security values, especially among individuals with less emotional stability, whereas economic worries were more strongly correlated with Power values, in particular among individuals with less emotional stability. Findings for Achievement values suggested perceived behavioral control effects for individuals high in Emotional Stability. Our findings provide insights into possible longer-term psychological effects of the current pandemic. Emotional dynamics in connection with worries created by the pandemic could influence values of importance for societal functioning in the short to medium term.